Halal Consumption Behavior of Muslim Millennials: Between Religiosity, Identity, and Digitalization - Astiwara, Endy Muhammad (Global Writing Academica Researching & Publishing, 2023)
This study aims to understand the consumption behavior of halal products among the Muslim millennial generation in Indonesia using a mixed-method approach. Quantitative data were obtained through an online survey of 60 respondents spread across five major cities, while qualitative data were collected through in-depth interviews with a number of selected respondents. Quantitative analysis revealed that awareness of halal, positive attitudes towards halal products, religiosity, and social influence play a significant role in shaping the intention to purchase halal products. Qualitative analysis enriches the findings by showing that halal consumption is not only a product choice, but also part of an individual's religious identity and moral responsibility. Interviews also identified practical obstacles such as limited access to verified halal products, unclear labels, and higher prices. The synergy of these two approaches confirms that halal consumption behavior is influenced by psychosocial factors and real challenges in the field. The results of the study provide strategic recommendations for business actors and policy makers to improve education and transparency of halal certification, as well as utilize social media as an effective communication channel to encourage wider halal consumption behavior among Muslim millennials.